Is plant reproductive efficiency expressed on a continuum of facilitation and competition?. (1st June 2021) - Al‐Namazi, Ali; Fazlioglu, Fatih; Bonser, Stephen Patrick
Abstract: Questions: Competition and facilitation form a continuum of interactions between plants from intensely negative to intensely positive. Competition has long been understood to be a major selective force driving the expression of adaptive strategies in plants. However, we remain uncertain if facilitation plays a similar role. In previous studies, the relative allocation to reproduction across plant species increases with increasing competition intensity, and this observation is generally consistent with life history theory (rather than traditional plant strategy theory). However, is facilitation also an important force in shaping adaptive strategies in plants? Methods: We surveyed the literature for plant facilitation studies that included measures of plant performance (e.g. vegetative biomass, height) and reproduction (e.g. reproductive biomass, seed number). We tested for a relationship between relative reproductive efficiency (the allocation to reproduction in the presence of neighbours relative to the allocation of reproduction in the absence of neighbours), and facilitation interaction intensity (i.e. the increase in plant performance due to the presence of neighbours). We also compared this relationship to the previously published relationship between reproductive efficiency and competition intensity to test for a continuum of strategies on an axis of plant–plant interactions from intensely positive (facilitation) to intensely negative (competition). Results: The overall relationship between facilitation intensity and the relative reproductive efficiency is a common negative relationship for both annual and perennial life histories. We found a highly significant negative relationship across the competition–facilitation continuum, with reproductive efficiency in the presence of neighbouring vegetation high under intense competition and low under intense facilitation. Conclusion: Plant reproductive strategies are expressed on a continuum of interactions from facilitation to competition. This continuum of interactions will be important in understanding how interactions between plants drive the evolution of adaptive strategies and control coexistence and diversity in plant communities. Abstract : Interactions between plants can be intensely negative (competition) through to intensely positive (facilitation). While competition is predicted to be important in the evolution of plant strategies, the potential role of facilitation in the expression and evolution of adaptive strategies is poorly understood. We demonstrate that plant reproductive strategies are expressed on a continuum of competitive to facilitative plant interactions.